Effect of ionization waves on dust chain formation in a DC discharge. (15th December 2021) - Matthews, L.S.; Vermillion, K.; Hartmann, P.; Rosenberg, M.; Rostami, S.; Kostadinova, E.G.; Hyde, T.W.; Pustylnik, M.Y.; Lipaev, A.M.; Usachev, A.D.; Zobnin, A.V.; Thoma, M.H.; et al.
Abstract : An interesting aspect of complex plasma is its ability to self-organize into a variety of structural configurations and undergo transitions between these states. A striking phenomenon is the isotropic-to-string transition observed in electrorheological complex plasma under the influence of a symmetric ion wake field. Such transitions have been investigated using the Plasma Kristall-4 (PK-4) microgravity laboratory on the International Space Station. Recent experiments and numerical simulations have shown that, under PK-4-relevant discharge conditions, the seemingly homogeneous direct current discharge column is highly inhomogeneous, with large axial electric field oscillations associated with ionization waves occurring on microsecond time scales. A multi-scale numerical model of the dust–plasma interactions is employed to investigate the role of the electric field in the charge of individual dust grains, the ion wake field and the order of string-like structures. Results are compared with those for dust strings formed in similar conditions in the PK-4 experiment.